Children, Schools, and Poverty = L'enfance, l'ecole, et la pauvrete - Hess, Melanie; Canadian Teachers' Federation, Ottawa (Ontario). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
This monograph (in both English and French) examines the impact of poverty on children, with particular reference to the situation of poor children in Canadian elementary and secondary schools. Section 1 briefly introduces the topics of education and poverty. The link between poverty and children's physical and mental health and educational attainment is examined in Section 2. Section 3 discusses problems poor children experience in relation to school. These include hunger; inadequate child care; low self-esteem, motivation, expectations, and achievement; delayed cognitive development; interrupted school attendance; and illiteracy. Section 4 suggests that aspects of the home environment and school experience explain the poor school performance of children from low-income families. Section 5 profiles intervention programs that attempt to redress the problems experienced by poor children in school. These programs include: (1) school-based, and combined school- and home-based, interventions; (2) compensatory education in preschool and elementary grades; and (3) interventions that address literacy, school-to-work transition, and the situation of school dropouts. Several authors' opinions on equality of educational opportunity are presented in Section 6. Conclusions are listed in Section 7. Appended materials include a series of tables presenting data on poverty in Canada; a 44-item reference list; and the Canadian Teachers' Federation's policy on children and poverty. (BC)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Child Health; Compensatory Education; Dropout Programs; Economically Disadvantaged; Education Work Relationship; Elementary School Students; Elementary Secondary Education; Equal Education; Foreign Countries; Intervention; Poverty; Preschool Education; Program Descriptions; Secondary School Students; Student Behavior; Canada; Opinion Papers; Reports, Descriptive; Multilingual/Bilingual Materials